1999
DOI: 10.1007/s002210050617
|View full text |Cite
|
Sign up to set email alerts
|

The thought translation device: a neurophysiological approach to communication in total motor paralysis

Abstract: A thought translation device (TTD) for braincomputer communication is described. Three patients diagnosed with amyotrophic lateral sclerosis (ALS), with total motor paralysis, were trained for several months. In order to enable such patients to communicate without any motor activity, a technique was developed where subjects learn to control their slow cortical potentials (SCP) in a 2-s rhythm, producing either cortical negativity or positivity according to the task requirement. SCP differences between a baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
2
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(154 citation statements)
references
References 19 publications
0
147
2
5
Order By: Relevance
“…figure 3). Using signal analysis and cursor control methods that were developed in BCI studies employing scalp-recorded EEG activity [33][34][35][36], this study found that ECoG-based control develops more quickly than EEG-based control [37,38], and is likely to be substantially more effective in providing communication and control to people with severe motor disabilities. Offline analysis of ECoG data recorded during a twodimensional (2D) center-out joystick task showed substantial directional information (figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…figure 3). Using signal analysis and cursor control methods that were developed in BCI studies employing scalp-recorded EEG activity [33][34][35][36], this study found that ECoG-based control develops more quickly than EEG-based control [37,38], and is likely to be substantially more effective in providing communication and control to people with severe motor disabilities. Offline analysis of ECoG data recorded during a twodimensional (2D) center-out joystick task showed substantial directional information (figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Further, this system has been tested in people with late-stage ALS and has proved capable of providing basic communication capacities [17]. Often, these BCIs are based on visual feedback from a computer screen that shows one choice at the top and one at the bottom.…”
Section: Scp-based Bcismentioning
confidence: 99%
“…Moreover, the more automated a task is, the less is the involvement of high-level control centres, the smaller the amount of involved synapses and relays, the faster the task execution. However, BMI control efficiency reduction due to fatigue has been reported also in automatic control systems (Kennedy et al, 2000): this is, sometimes, caused by user attempt to speed up the control (Kübler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%